IMPLEMENTASI PROGRAM PEMBIASAAN TERSTRUKTUR BERBASIS KARAKTER ISLAMI DI MTS NEGERI 3 WONOGIRI - Suwarni Suwarni; Imam Makruf (Jurnal Syntax Transformation, 2023)
This study aims to describe the implementation of a structured habituation program based on Islamic character at MTs Negeri 3 Wonogiri, with sub-focuses including: (1) the form of a structured habituation program based on Islamic character (2) Islamic characters formed in students through a structured habituation program ( 3) Evaluation of the implementation of a structured habituation program for the formation of Islamic character values. The method used in this study is a qualitative method with a descriptive approach. To check the validity of the data, it is done by means of triangulation and reference materials. While the research informants are the head of the madrasa, deputy head in the field of student affairs, teachers and homeroom teachers, as well as other parties related to this research. The results of this study indicate that: the implementation of a structured habituation program based on Islamic character based on the implementation time includes: daily, monthly and yearly programs as well as incidental activities aimed at the formation of morality and worship, the characters that can be grown with the program are: religious culture, caring, honest, disciplined, creative, national spirit, social care, and responsibility, while the form of evaluation is carried out through Monday ceremonies, teacher meetings and through the BTQku achievement book